The key success factors in the promotions carried out with last generation mobile devices: a theoretical analysis - Roman Coy, David; García Medina, Irene (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2013)
The use of mobile devices has grown exponentially in the last 15 years. This development has reached the culmination with the introduction in 2007 of Smartphones and Tablets. Companies and organizations have a new channel with multiple commercial possibilities and are doing the best of it. The objective of this research was to analyze and understand this reality through academic literature. The results of the investigation will clarify the reasons why commercial promotions are successful and it will show us what the most important factors are that make mobile devices extend and improve the way in which companies perform promotional activities.
Keywords: Mobile promotions; Sales Promotions; Mobile Devices; Mobile Advertising; Mobile Marketing